DESAIN MODUL PRAKTIKUM BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Mutiya Mutiya; ELVI YENTI; neti afrianis (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2019)
Practicum guides that usually exist in school was student workbook taken from chemistry book that were too a lead and not using a learning model so that it did not motivate students to think creatively. Therefore, it was necessary  a teaching material design that completing learning model. It was a Practicum module Problem Based Learning based. This research aimed at knowing the validity, prcaticality levels and student respond toward practicum module produced. It was a Research and Development (R&D) with Borg and Gall model. Subject of this research were a lecturer of material expert, a lecurer of  media expert, two teacher of chemistry and tenth students at the Eleventh Grade of MIA at State Senior High School 2 Kuok. The object of this reserach were practicum module Problem Based Learning  (PBL) based on electrolyte solution and non electrolyte lesson. Validity test questionnaire and practicality test questionnaire  and student respond questionnaire were the techniques of collecting the data. Data analysis was done by using Descriptive qualitative and quantitative analysis techniques. The result of data analysis shows that the validity level of practicum module Problem  Based Learning  (PBL) Based was 92.38% (Very valid) and the practicality level  was 85.60% (Very practice). Based on this research, it could be concluded that the Practicum Module Problem Based Learning  (PBL) Based on Electrolyte Solution and Non Electrolyte Lesson were valid and practice and got a good student respond to be used as teaching material in practical activity at school. Keywords : Practicum Module, Problem Based Learning, Electrolyte Solution and Non Electrolyte Lesson.